Long-term Prognosis of Paroxysmal Atrial Fibrillation and Predictors for Progression to Persistnt or Chronic Atrial Fibrillation in the Korean Population - Im, Sung II (J Korean Med Sci, 2015)
Little is known about the long-term prognosis of or predictors for the different clinical types of atrial fibrillation (AF) in Korean populations. The aim of this study was to validate a risk stratification to assess the probability of AF progression from paroxysmal AF (PAF) to persistent AF (PeAF) or permanent AF. A total of 434 patients with PAF were consecutively enrolled (mean age; 71.7 ± 10.7 yr, 60.6% male). PeAF was defined as episodes that are sustained > 7 days and not self-terminating, while permanent AF was defined as an ongoing long-term episode. Atrial arrhythmia during follow-up was defined as atrial premature complex, atrial tachycardia, and atrial flutter. During a mean follow-up of 72.7 ± 58.3 months, 168 patients (38.7%) with PAF progressed to PeAF or permanent AF. The mean annual AF progression was 10.7% per year. In univariate analysis, age at diagnosis, body mass index, atrial arrhythmia during follow-up, left ventricular ejection fraction, concentric left ventricular hypertrophy, left atrial diameter (LAD), and severe mitral regurgitation (MR) were significantly associated with AF progression. In multivariate analysis, age at diagnosis (P = 0.009), atrial arrhythmia during follow-up (P = 0.015), LAD (P = 0.002) and MR grade (P = 0.026) were independent risk factors for AF progression. Patients with younger age at diagnosis, atrial arrhythmia during follow-up, larger left atrial chamber size, and severe MR grade are more likely to progress to PeAF or permanent AF, suggesting more intensive medical therapy with close clinical follow-up would be required in those patients.